Pengaruh Media Video Youtube terhadap Hasil Belajar Siswa Pembelajaran Pendidikan Pancasila Sekolah Dasar Negeri 06 Pontianak Selatan - Salsabila, Salma; Salimi, Asmayani; Kresnadi, Hery; Pranata, Rio (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study aims to determine learning outcomes, whether there is an influence, and how much influence of the use of YouTube video media to the learning outcomes of class V college students of the country 06 Pontianak south. The method of this research is the experimental method with the type of quasi experimental research. The data analysis technique used in this research is measurement / test-shaped technique of multiple choice. The instrument of this research is about pre test and posttest. The results showed the result of student learning students of v. Primary School of the country 06 Pontianak south searched the difference between experimental and control classes showing some advantages affecting learning outcomes by applying video media and not video client media, Microwuate video media affect the learning outcomes of class V college students Primary School 06 Pontianak South is with significance value of 0.013, and great from the effect of YouTube video media to student learning outcomes of class V college of the country 06 Pontianak South is 1 of which is included in the category high.